Referral to medical outpatients department at teaching hospitals in Birmingham and Amsterdam. Issue 6542 (2nd August 1986) - Hull, F M; Westerman, R F
Abstract : A method of comparing the referral of patients by general practitioners to medical outpatients departments at teaching hospitals in Amsterdam and Birmingham was devised. This was applied to 89 referral letters to medical specialists at the Free University Medical School Policlinic in Amsterdam and to 88 referral letters to clinics at Birmingham University Medical School, UK. The standards of referral were lower in the Netherlands than in Britain, and this may be related to differences in the health care systems, in the culture, or in the organisation of general practice. The delay between the general practitioner's referral and the consultation to the outpatient department was four times greater in Britain than in the Netherlands.